Canonical nonequilibrium statistics and applications to Fermi-Bose systems - Ebeling, W. (Condensed Matter Physics, 2000)
The aim of this work is the study of a special class of nonequilibrium systems which admits to ﬁnd exact stationary solutions of the kinetic equations. In particular we investigate canonical-dissipative systems, where the
driving terms are determined by the Hamiltonian or other invariants of motion only. We construct systems which drive the system to special invariants of motion and solve the corresponding Fokker-Planck equations. Finally several applications to mean-ﬁeld problems for fermion and for boson
systems are discussed. Метою цієї роботи є вивчення особливого класу нерівноважних систем, який допускає знаходження стаціонарних розв’язків кінетичних рівнянь. Зокрема, ми досліджуємо канонічно-дисипативні системи, в яких ведучі члени визначаються гамільтоніаном або іншими інваріантами руху. Ми будуємо системи, які приводять систему до особливих інваріантів руху, і розв’язуємо відповідні рівняння Фокера-
Планка. Нарешті, ми обговорюємо деякі застосування до середньо-польових проблем для систем ферміонів і бозонів.